Variational Iteration Method for Initial and Boundary Value Problems Using He's Polynomials - Syed Tauseef Mohyud-Din; Ahmet Yildirim; M. M. Hosseini (International Journal of Differential Equations)
This paper outlines a detailed study of the coupling of He's polynomials with correction functional of variational iteration method (VIM) for solving various initial and boundary value problems. The elegant coupling gives rise to the modified versions of VIM which is very efficient in solving nonlinear problems of diversified nature. It is observed that the variational iteration method using He's polynomials (VIMHP) is very efficient, easier to implements, and more user friendly. Several examples are given to reconfirm the efficiency of the proposed VIMHP.